Asymmetric Effect of External Debt and Foreign Capital Flows on Economic Growth: New Evidence from Nigeria - Elias A. Udeaja; Nathan Audu (Athens Journal of Business & Economics, 2023)
This research examines the asymmetric nexus between external debt and foreign capital flows on economic growth in Nigeria. The paper employed the non-linear autoregressive distributed lag (NARDL) methodology to investigate the asymmetrical effect of external debt on real Gross Domestic Product (GDP) growth in Nigeria. The estimated long-run parameters for positive and negative shocks of external debt are -1.08 and 3.09, respectively. The outcome indicated that a percentage increase in external debt will result in a 1.08 decrease in real GDP growth and that a one percent decrease in external debt will result in a 3.08 increase in economic growth. This illustrates that the receptiveness of real GDP growth to positive values of external debt is different to that of negative values of external debt. The reaction of real GDP growth to negative values of external debt is larger than to positive value of external debt. This suggests that it is imperative for Nigeria to have manageable external debt and fiscal sustainability as this would bolster its real economic growth as well as urge the fiscal authority to make concerted effort towards curbing corruption and reducing inefficiency to the barest minimum, as these will enhance growth.